Effects of golf ball dimple surface occupancy, volume ratio and depth on aerodynamic characteristics during rotation - Moriyama, K.; Okanaga, H. (Sports Engineering, 2023)
For golfers, the length of the flight distance is very important for improving scores. Therefore, the surface of a golf ball is provided with innumerable dents called dimples to improve the flight distance. These dimples can be characterized by the dimple occupancy and dimple volume ratio. Therefore, we manufactured model balls in which the dimple occupancy was changed by the dimple diameter and the number of dimples, and the dimple depth was changed to change the dimple volume ratio. Fifteen model balls were designed using 3D CAD and then 3D printed. Using these balls, we carried out lift and drag measurements in wind tunnel experiments. Then, a flight trajectory simulation was performed based on the obtained experimental results, and the effects of the dimple occupancy and dimple volume ratio on the flight distance were elucidated. In rotating golf balls, when the dimple depth was shallow, i.e., D/d = 4.55 × 10^-3, and the occupancy ratio was 80% or higher, the lift-drag ratio was higher, and the flying distance was increased. However, when the dimple depths were D/d = 6.82 × 10^-3 and D/d = 9.09 × 10^-3, there was almost no effect of the occupancy ratio. Furthermore, when comparing these two depths, the lift-drag ratio was bout 15% lower for deeper dimples. With respect to the dimple volume ratio, the drag coefficient increased with increasing dimple volume ratio. The lift-drag ratio was also highest in the dimple volume ratio range of 11.0-12.0 × 10^-3.